Terapi Intravenous Immunoglobulin (IVIG) pada Pasien Covid-19 di Intensive Care Unit (ICU) - Ferianto Ferianto; Suwarman Suwarman; Sobaryati Sobaryati (Fakultas Kedokteran Universitas Riau, 2021)
Intravenous immunoglobulin (IVIG) is a plasma derivative product that can provide passive immune protection against various pathogens. IVIG was given to COVID-19 patients who are seriously and critically ill. In this case report, a 43-year-old male patient who has been confirmed with COVID-19 is admitted to the COVID-19 ICU. The patient complains of tightness, coughing and weakness. The examination found decreased SpO2, hypertension and Chest X-ray revealed bilateral bronchopneumonia. On the first day the patient was given antiviral remdesivir 200mg drip IV/3 hours, amlodipine 1x 5mg, codeine 3x10 mg, combivent 3x1, furosemide, and albumin 25% 2 kolf. On days two to five patients were given antiviral remdesivir 100mg drip IV/3 hours, IVIG, namely Gamaras 5 flash, heparin 25,000 units. On the tenth day of treatment in the ICU, the patient’s complaints had decreased. On the eleventh day the patient had no complaints and the patient’s vital signs concluded that the problem was resolved.